New Wild Garden : Natural-Style Planting and Practicalities. - Hodgson, Ian (Quarto Publishing Group UK, 2021)
New Wild Garden combines new approaches to a more naturalistic design with the practical side of growing wildflowers and shows how to incorporate wildflowers, real meadows and a looser meadow-style planting into gardens and wild spaces.